Strategies for indica rice adapted to high-temperature stress in the middle and lower reaches of the Yangtze River - Zhang, Man; Li, Zhong; Feng, Kaixuan; Ji, Yalan; Xu, Youzun; Tu, Debao; Teng, Bin; Liu, Qiumeng; Liu, Jingwen; Zhou, Yongjin; Wu, Wenge (Frontiers in Plant Science, 2023)
High temperature seriously affects the yield and quality of rice. The field experiment in this study confirmed that carpet seedling mechanical transplanting and delayed sowing date treatment can effectively increase the leaf area index of rice and reduce the canopy temperature. At the same time, pot experiments confirmed that mechanical transplanting with carpet seedling and delayed sowing treatment can also improve the rice yield and quality. On this basis, this study confirmed that brassinolide and salicylic acid had the most obvious effect through a variety of plant auxin regulator screening experiments, which could significantly improve the activity of antioxidant enzymes in rice panicles, reduce the damage caused by the accumulation of reactive oxygen species under high temperature, enhance plant resistance to high temperature, improve anther dehiscence rate, and ultimately improve seed setting rate. A set of green simplified cultivation techniques for single cropping indica rice adapted to high temperature stress was established in this study, which was of great significance for reducing the effect of high temperature stress on rice production.